# Difference between revisions of "User talk:Meljel"

(Blanked the page) (Tag: Blanking) |
(→It's me meljel lol: new section) |
||

Line 1: | Line 1: | ||

+ | == It's me meljel lol == | ||

+ | <cmath> \begin{align*} | ||

+ | ax^2 + bx + c &= 0\\ | ||

+ | a(x^2 + \frac bax + \frac ca) &= 0\\ | ||

+ | a({(x + \frac {b}{2a})}^2 - \frac{b^2}{4a^2} + \frac ca) &= 0\\ | ||

+ | {(x + \frac {b}{2a})}^2 - \frac{b^2}{4a^2} + \frac ca &= 0\\ | ||

+ | {(x + \frac {b}{2a})}^2 &= \frac{b^2}{4a^2} - \frac ca\\ | ||

+ | {(x + \frac {b}{2a})}^2 &= \frac{b^2}{4a^2} - \frac {4ac}{4a^2}\\ | ||

+ | {(x + \frac {b}{2a})}^2 &= \frac{b^2 - 4ac}{4a^2}\\ | ||

+ | x + \frac {b}{2a} &= \pm\sqrt{\frac{b^2 - 4ac}{4a^2}}\\ | ||

+ | x + \frac {b}{2a} &= \pm\frac{\sqrt{b^2 - 4ac}}{2a}\\ | ||

+ | x &= - \frac {b}{2a} \pm\frac{\sqrt{b^2 - 4ac}}{2a}\\ | ||

+ | x &= \frac{- b \pm \sqrt{b^2 - 4ac}}{2a}\\ | ||

+ | \end{align*} | ||

+ | </cmath> | ||

+ | |||

+ | == It's me meljel lol == | ||

+ | |||

+ | hi |

## Revision as of 00:48, 8 January 2019

## It's me meljel lol

## It's me meljel lol

hi